Environmental Wind Engineering and Design of Wind Energy Structures - Baniotopoulos, Charalambos C.; Borri, Claudio; Stathopoulos, Theodore; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2011)
The book presents a state-of-the-art in environmental aerodynamics and the structural design of wind energy support structures, particularly from a modern computational perspective. Examples include real-life applications dealing with pollutant dispersion in the building environment, pedestrian-level winds, comfort levels, relevant legislation and remedial measures. Design methodologies for wind energy structures include reliability assessment and code frameworks.
T. Stathopoulos: Introduction to environmental aerodynamics -- T. Stathopoulos: Applications of environmental aerodynamics -- B. Blocken: Computational wind engineering. Theory and applications -- A. Zasso, P. Schito: Aero-servo-elastic design of wind turbines: numerical and wind tunnel modeling contribution -- P. Schaumann et al.: Support structures of wind energy converters -- C. C. Baniotopoulos et al.: Topics of the design of tubular steel wind turbine towers -- C. Borri, P. Biagnini, E. Marion: Large wind turbines in earthquake areas: structural analyses, design/construction and in-situ testing.
Keywords: Engineering; Hydraulic engineering; Renewable energy sources; Engineering; Engineering Fluid Dynamics; Renewable and Green Energy; Building Construction; Energy Efficiency (incl. Buildings).